2001
DOI: 10.1002/1527-2648(200108)3:8<587::aid-adem587>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Static Recrystallization

Abstract: Thermomechanical treatments basically aim at refining the grain size and controlling the crystallographic texture of metallic materials. First developed for the austenitic rolling of C±Mn steels, they are now being extended to a wide range of metals, e.g., aluminum, titanium, and nickel-based alloys. Dynamic or static recrystallizations are certainly the main mechanisms responsible for the microstructure and texture changes occurring during or after deformation. It is therefore not surprising that several team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In high SFE metals, e.g., aluminum, [39] where the dislocation mobility was much larger, dynamic recovery (DRV) was assumed to be the only operating mechanism. [40] However, recent studies indicated the presence of fine dynamically recrystallized grains possessing predominantly HAGBs and a low dislocation density in the friction-stir-welded aluminum alloys. [6,8,41] In the present study, the fine and equiaxed grains in the NZ of the friction-stir-welded 6061Al-T651 alloy were achieved and they were considerably smaller than those in the BM.…”
Section: A Microstructural Characteristicsmentioning
confidence: 99%
“…In high SFE metals, e.g., aluminum, [39] where the dislocation mobility was much larger, dynamic recovery (DRV) was assumed to be the only operating mechanism. [40] However, recent studies indicated the presence of fine dynamically recrystallized grains possessing predominantly HAGBs and a low dislocation density in the friction-stir-welded aluminum alloys. [6,8,41] In the present study, the fine and equiaxed grains in the NZ of the friction-stir-welded 6061Al-T651 alloy were achieved and they were considerably smaller than those in the BM.…”
Section: A Microstructural Characteristicsmentioning
confidence: 99%
“…Since the rate of annihilation due to dynamic recovery is not sufficient to complete with the strain hardening rate in low SFE materials, the dislocation density increases continuously in this case. Contrary, high SFE materials act in favor for higher mobility of dislocation, and consequently dynamic recovery becomes involved as an operating mechanism [49]. The details of materials and the type of possible phenomena are illustrated in Table 2.…”
Section: Recrystallizationmentioning
confidence: 99%
“…The details of materials and acting mechanisms during the hot deformation process [34,49,50].…”
Section: Recrystallizationmentioning
confidence: 99%
“…The hot flow behavior of materials, commonly obtained through axisymmetric compression testing (ACT), is essential to characterize and study related phenomena such as microstructure development, phase change, [1,2] material recovery, static, dynamic and metadynamic recrystallization (SRX and (M) DRX [3] ). The effective stress-strain curve provides insight into the activation energy required for deformation processes in the material.…”
Section: Introductionmentioning
confidence: 99%